Use of Adipose-Derived Mesenchymal Stem Cells in Keratoconjunctivitis Sicca in a Canine Model - Villatoro, Antonio J.; Fernández, Viviana; Claros-Gil, Silvia; Rico-LLanos, Gustavo Adolfo; Becerra-Ratia, José; Andrades-Gómez, José Antonio (Wiley, 2015)
Keratoconjunctivitis sicca (KCS) or dry eye disease (DED) is an immune-mediated multifactorial disease, with high level of prevalence in humans and dogs. Our aim in this study was to investigate the therapeutic effects of allogeneic adipose-derived mesenchymal stromal cells (Ad-MSCs) implanted around the lacrimal glands in 12 dogs (24 eyes) with KCS, which is refractory to current available treatments. Schirmer tear test (STT) and ocular surface integrity were assessed at 0 (before treatment), 3, 6, and 9 months after treatment. Average STT values and all clinical signs showed a statistically significant change (𝑃 < 0.001) during the follow-up with reduction in all ocular parameters scored: ocular discharge, conjunctival hyperaemia, and corneal changes, and there were no signs of regression or worsening. Implanted cells were well tolerated and were effective reducing clinical signs of KCS with a sustained effect during the study period. None of the animals showed systemic or local complications during the study. To our knowledge, this is the first time in literature that implantation of allogeneic Ad-MSCs around lacrimal glands has been found as an effective therapeutic alternative to treat dogs with KCS. These results could reinforce a good effective solution to be extrapolated to future studies in human.
Keywords: Células madre; Keratoconjunctivitis sicca; Dry eye disease; Mesenchymal stem cells; Adipose-derived mesenchymal stem cells